Distribution and Density of (Pilsbryochonca Exillis) in the Indragiri River, Lubuk terentang Village, Gunung Toar District, Kuantan Singingi Regency,Riau Provinve - Reggy Erianti Putri; Eni Sumiarsih; M. Fauzi M. Fauzi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTIndragiri River has high biological resources as necton, gastropods, plankton and the others. There are activities antropogenic can affect the distribution of Pilsbryochonca exillis. P. exillishas good ecological and economic potential. This study aimedto determine the distribution and density of P. exillis in the Indragiri river, Lubuk Terentang village, Kuantan Singingi Regency, Riau Province. Sampling used the plot method and hand sampling, a plot divided into 9 sub-plots (9x3m). The results shown that the distribution of P. exillisis uniform and clumped. The distribution based on Morishitaindexis about 0,47 to 1,06. The highest density found in Station I was 1,05 ind/m2 and the lowest was found in Station III was 0,22 ind/m2. It is also known that the distribution and density of P. exillis in Indragiri River Waters are not disturbed. Keywords: River Organisms, Distribution,Characteristic, Density and Gastropods